Impact of Electric Vehicle Adoption on Electricity Consumption and Generation: Evidence from California - Ferdousee, Atia (International Journal of Energy Economics and Policy, 2022)
The market share of electric vehicles (EV) is growing in the USA, and there are substantial numbers of federal, and state-level incentives for EV consumers. These incentives are in place primarily due to environmental concerns. This study focuses on two interrelated aspects of EV adoption. First, using monthly county-level data from 2010 to 2019, this study reveals that electric vehicles and their supportive infrastructures, such as charging stations, have a significant effect on residential and commercial electricity consumption in California. Second, analyzing electricity generation information by county, this study finds a significant negative relation between electricity usage and the share of electricity that comes from renewable sources. Although EVs emit lower pollutants than conventional vehicles, they require a significant amount of electricity for charging. If the electricity generation doesn’t involve renewable or cleaner sources, public spending on EV may not contribute to a cleaner environment as much as expected.